2021
DOI: 10.1128/iai.00441-21
|View full text |Cite
|
Sign up to set email alerts
|

Bile Salts Promote ToxR Regulon Activation during Growth under Virulence-Inducing Conditions

Abstract: Cholera is an epidemic disease caused by the Gram-negative bacterium Vibrio cholerae . V. cholerae is found in aquatic ecosystems and infects people through the consumption of V. cholerae contaminated food or water. Following ingestion, V. cholerae responds to host cues to activate the expression of critical virulence genes that are under control of a hierarchical regulatory system called the ToxR regulon. The ToxR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Also indicative of ToxR regulon activity and bile resistance, ompU expression was increased in overnight comparisons, although the corresponding downregulation of ompT 30 was only observed in one of the overnight comparisons (Supplementary Figure S4B). Bile and anaerobicity are both known activators of the ToxR regulon 42,43 , which is consistent with the observation of its transcriptional upregulation in these conditions. ToxR induces a regulatory cascade for V. cholerae virulence gene expression induced in the human gut in the context of infection 12 , and has been shown to be highly transcriptionally upregulated in both rabbit and mouse animal models of cholera 44 .…”
Section: Rna Sequencing Of V Cholerae Grown In Anaerobic Bile and Ana...supporting
confidence: 90%
“…Also indicative of ToxR regulon activity and bile resistance, ompU expression was increased in overnight comparisons, although the corresponding downregulation of ompT 30 was only observed in one of the overnight comparisons (Supplementary Figure S4B). Bile and anaerobicity are both known activators of the ToxR regulon 42,43 , which is consistent with the observation of its transcriptional upregulation in these conditions. ToxR induces a regulatory cascade for V. cholerae virulence gene expression induced in the human gut in the context of infection 12 , and has been shown to be highly transcriptionally upregulated in both rabbit and mouse animal models of cholera 44 .…”
Section: Rna Sequencing Of V Cholerae Grown In Anaerobic Bile and Ana...supporting
confidence: 90%
“…Interestingly, ToxR’s periplasmic sensing domain is required for activation of leuO transcription suggestive of an efflux-dependent small molecule feedback mechanism tying ToxR to leuO expression. Consistent with these observations, ToxR induced leuO expression in the presence of multiple RND efflux substrates including bile acids, indole, and diketopiperazines, the former two being RND efflux substrates that are abundant in the human gastrointestinal tract ( Bina et al., 2009 ; Bina and Bina, 2010 ; Bina et al., 2013 ; Ante et al., 2015b ; Howard et al., 2019 ; Bina et al., 2021 ). Furthermore, the RND efflux inhibitor phenylalanine-arginine β-naphthylamide induced leuO expression by a mechanism dependent on the presence of the ToxR periplasmic sensing domain suggestive of a regulatory feedback circuit that inhibits efflux of the transporter’s native substrates to modulate the ToxR regulon.…”
Section: Rnd Efflux Activity Modulates Adaptive Responses V...supporting
confidence: 65%
“…In this study, we also found that ToxR protein, a key transcription activator, is acetylated. Bile salt can promote the activation of toxR regulator and participate in the regulation of bacterial virulence genes ( 48 , 49 ). Bacterial toxin factor ( AOG25_14550 ) is a Hcp1 family type VI secretion system effector, which also acetylated under bile salt stress in V. alginolyticus .…”
Section: Discussionmentioning
confidence: 99%